2022
DOI: 10.3389/fendo.2022.882379
|View full text |Cite
|
Sign up to set email alerts
|

Morphological and Immunophenotypical Changes of Human Bone Marrow Adipocytes in Marrow Metastasis and Myelofibrosis

Abstract: The bone marrow adipose tissue constitutes more than two-thirds of the bone marrow volume in adult life and is known to have unique metabolic and functional properties. In neoplastic disorders, bone marrow adipocytes (BMAds) contribute to create a favorable microenvironment to survival and proliferation of cancer cells. Many studies explored the molecular crosstalk between BMAds and neoplastic cells, predominantly in ex-vivo experimental systems or in animal models. However, little is known on the features of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 42 publications
0
1
0
Order By: Relevance
“…Therefore, it has been shown that BMAdscan modulate the migration and aggressiveness of neoplastic cells ( 16 ). Dello Spedale Venti et al ( 17 ) reported the possibility of BMAds being associated with tumour BMM.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, it has been shown that BMAdscan modulate the migration and aggressiveness of neoplastic cells ( 16 ). Dello Spedale Venti et al ( 17 ) reported the possibility of BMAds being associated with tumour BMM.…”
Section: Discussionmentioning
confidence: 99%